Investigating the role of sociodemographic factors in medical students' perception of an AR mobile-based tool - Mohd Thani, Suryati; Abd Manan, Nizar; Muhamad Saliluddin, Suhainizam; Saat, Azmah (Penerbit Universiti Kebangsaan Malaysia, 2025)
Augmented Reality (AR) is an emerging technology with significant potential in education, particularly in enhancing student engagement and learning experiences. However, for AR-based learning tools to be effective, their perceived ease of use and usefulness must be considered. This study aims to evaluate the association between sociodemographic factors — including gender, year of study, and socioeconomic status—and the perceived ease of use and usefulness of the AR app as a teaching and learning tool among medical students at the Faculty of Medicine and Health Sciences, Universiti Putra Malaysia. A cross-sectional study was conducted using a convenience sampling method, involving both clinical and pre-clinical students from the Faculty of Medicine and Health Sciences at Universiti Putra Malaysia. A total of 173 students participated in the study. Among them, 87.3% found the app easy to use, and 78.6% perceived it as useful. Chi-square analysis showed no significant association between perceived ease of use and gender, year of study, or socioeconomic status. Similarly, there was no significant association between perceived usefulness and these sociodemographic factors. The findings indicate that perceived ease of use and usefulness of the AR app are independent of gender, year of study, and socioeconomic status. These results suggest that the app provides a universally accessible and beneficial learning experience for medical students, reinforcing the potential of AR technology in medical education. Future studies should explore additional factors, such as learning styles and prior exposure to AR, to further optimize its implementation in medical training.